2010
DOI: 10.1007/s10072-010-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional motion analysis of the effects of auditory cueing on gait pattern in patients with Parkinson’s disease: a preliminary investigation

Abstract: Auditory cueing enhances gait in parkinsonian patients. Our aim was to evaluate its effects on spatiotemporal (stride length, stride time, cadence, gait speed, single and double support duration) kinematic (range of amplitude of the hip, knee and ankle joint angles registered in the sagittal plane) and kinetic (maximal values of the hip and ankle joint power) gait parameters using three-dimensional motion analysis. Eight parkinsonian patients performed 12 walking tests: 3 repetitions of 4 conditions (normal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 33 publications
1
40
2
Order By: Relevance
“…Accordingly, gait characteristics such as symmetry and cadence can be targeted by changing the inter-beat intervals of acoustic stimuli. The widespread use of acoustic cues in rehabilitation practice is backed up by a steadily growing body of literature reporting positive effects of acoustic rhythms on gait [6][7][8][9][10][11][12][13][14][15][16][17]. Remarkably in light of this development, the manner in which gait is adjusted to acoustic stimuli (i.e., auditory-motor coordination) has received limited attention, even though its understanding may lead to more effective applications of acoustic cues in rehabilitation practice.…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, gait characteristics such as symmetry and cadence can be targeted by changing the inter-beat intervals of acoustic stimuli. The widespread use of acoustic cues in rehabilitation practice is backed up by a steadily growing body of literature reporting positive effects of acoustic rhythms on gait [6][7][8][9][10][11][12][13][14][15][16][17]. Remarkably in light of this development, the manner in which gait is adjusted to acoustic stimuli (i.e., auditory-motor coordination) has received limited attention, even though its understanding may lead to more effective applications of acoustic cues in rehabilitation practice.…”
Section: Introductionmentioning
confidence: 96%
“…The finding that the improvements remained even when the cues were removed suggests that rhythmic auditory stimulation may also provide a sort of rhythmic training mechanism. Picelli et al (Picelli et al, 2010) recently performed a preliminary investigation about the threedimensional motion analysis of the effects of auditory cueing on gait pattern in patients with PD who underwent auditory cueing respectively at 90, 100 and 110% of their mean cadence at preferred pace. The authors reported that in the presence of auditory cues, walking speed and stride length showed an increase that became more significant matching the higher cueing frequencies.…”
Section: Auditory Cueingmentioning
confidence: 99%
“…To make the model representation independent of the original image, image descriptors such as silhouettes, edges, color and texture are frequently used in 2D Ml approaches [9]. In answering to some specific clinical questions, 3D gait analysis showed that the most significant differences between groups were concentrated in the sagittal joint kinematics [10][11][12], therefore, in such cases, the information provided by a 2D quantitative sagittal joint kinematics analysis may be sufficient, as long as that the main joint axis remains approximately perpendicular to the image plane throughout the recording of the motor task.…”
Section: Introductionmentioning
confidence: 99%